Systemic lupus erythematosus/Seborrheic dermatitis. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2004)
Due to the rarity of systemic lupus erythematosus (SLE) in males, the differential diagnosis between SLE and seborrheic dermatitis (SD) is mainly actual in females. Also the age is important, as both SLE and SD are exceptional before puberty. In pediatric dermatology the differential diagnosis between these two disorders is thus actual around puberty, when SLE gets more frequent and SD may start.